Serving multinational society as principle of further perfection of Kazakhstan – the legal state (Journal of actual problems of jurisprudence, 2018)
The article deals with the foreign and domestic policy of the Republic of Kazakhstan and legal changes in the civil society. The specific features of globalization and integration have been analyzed. The necessity of joint use of the methods of legal and political analysis in the process of interpretation are revealed and studied. The author proposes to highlight the Republic of Kazakhstan as the subject of international law on the basis of undertaken research.Key words: tolerance, assembly, radicalism, strategy, globalization, civilization, modernization, totalitarianism, political mode, international consent, tendency.